Manajemen Perencanaan Pendidikan melalui Penyusunan Rencana Kerja Madarasah/Sekolah di Madrasah dan Sekolah - Abdul Hasan; Zahra Nauli; Zam Zarinah; Leni Sulistia Ningsih; Aprizal Ahmad; Rully Hidayatullah (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
Educational planning management is an essential process in managing educational institutions to achieve educational goals effectively and efficiently. One form of implementing educational planning management is through the preparation of the Madrasah Work Plan (RKM) and School Work Plan (RKS). This article aims to describe the concept of educational planning management through the preparation of RKM/RKS, their objectives, preparation processes, and implementation in schools and madrasahs. The research method used is library research with a qualitative descriptive approach by collecting data from books, scientific journals, government regulations, and other supporting documents. The results of the study indicate that RKM/RKS has a strategic role as a guideline for implementing educational programs, a basis for decision-making, an evaluation tool, and an instrument for improving the quality of education. The preparation of RKM/RKS is carried out systematically through team formation, school/madrasah self-evaluation, formulation of priority programs, preparation of medium-term and annual work plans, and budgeting plans. Proper implementation of RKM/RKS can improve the effectiveness of educational management, accountability, transparency, and the quality of educational services in schools and madrasahs.